Sociology and Contemporary Critical Theory - Salem, A.; Till, Chris (Sociologija. Mintis ir veiksmas, 2017)
This editorial summarises a series of eight papers for the Sociologija. Mintis ir veiksmas special issue, ‘Sociology and Contemporary Critical Theory’, the impetus for which came out of a symposium held in April 2017 at Leeds Beckett University, entitled ‘Critical and Philosophical Issues after Post-Structuralism’. The event was organised by the Critical Theory Research Group, its members’ intellectual interests spanning social and cultural theory, political theory, visual culture and social psychology; their aim was and is to reflect upon various tactics for politically engaged and socially active theoretical writing in the wake of a fundamental questioning of knowledge and certainty, and also more recently of the rise of cultural and political developments that would deny the rights of the Other.